A Study on the Ability in Using Prepositions of “Time” by the Second Year Students of Language Program at SMA Negeri Niki-Niki, Amanuban Tengah Subdistrict, Timor Tengah Selatan Regency, East Nusa Tenggara in the School Year 2023/2024: English - Isu, Rudolof Jibrael; Malelak, Deby M.; Langkameng, Oce A.; Radja, Markus D.; Ingunau, Temmy M. E. (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
It cannot be denied that we need a language to communicate with each other in our life. Lado (1964:9) stated that language is the chief means by which human personality expresses and fulfills its basic needs for social interaction with other people. By using language, someone’s opinion could be understood by others. Without language it is impossible for everyone to understand others’ opinion or idea. Everybody should realize that interaction and relation in a social will be empty without language. Preposition in this little words in English (Wishon and Burks, 1980: 288). In preposition of time many students find some troubles; they can’t construct the sentences correctly. Descriptive method and the instrument is test. The type of test is completion test, by which the writer asks the students to complete the sentences. The writer conducted the test only one time. The subjects of research is how far by the Second Year Students of Language Program at SMA Negeri Niki-Niki, Amanuban Tengah Subdistrict, Timor Tengah Selatan Regency, East Nusa Tenggara In The School Year 2023/2024 able to use the preposition of time? And the total numbers of students are 24 students. Keywords : language, time, preposition